NbPHAN, a MYB transcriptional factor, regulates leaf development and affects drought tolerance in Nicotiana benthamiana. Issue 3 (15th March 2013) - Huang, Changjun; Hu, Gaojie; Li, Fangfang; Li, Yunqin; Wu, Jianxiang; Zhou, Xueping
<x xml:space="preserve">Abstract</x> MYB transcriptional factors, characterized by the presence of conserved DNA‐binding domains (BDs) (MYB domain), are involved in diverse processes including plant growth, development, metabolic and stress responses. In this study, a new R2R3‐type MYB gene, NbPHAN (Nicotiana benthamiana PHANTASTICA), was identified in N. benthamiana. The NbPHAN encodes a protein of 362 amino acids and shares high sequence identities with the AS1‐RS2‐PHANs (ARPs) from other plant species. The NbPHAN protein targets to and forms homodimers in the nucleus. The MYB domain and C‐terminal region of NbPHAN determine its subcellular localization and homodimerization, respectively. Using virus‐induced gene silencing, we showed that the NbPHAN‐silenced leaves exhibited severe downward curling and abnormal growth of blades along the main veins through suppressing the expression of the NTH20 gene. In addition, we found NbPHAN plays an important role in drought tolerance. The NbPHAN‐silenced plants exhibited severe wilting and increased rate of water loss than that found in the non‐silenced plants when growing under the water deficit condition. Although abscisic acid accumulation was not altered in the NbPHAN‐silenced plants as compared with that in the non‐silenced plants, several other stress‐inducible genes were clearly repressed under the water deficit condition. Our results provide strong evidence that other than controlling leaf development, the ARP genes can also regulate plant tolerance to drought stress.